Fluxus Subjektiv - Krinzinger, Ursula (Wien : Galerie Krinzinger, 1990)
Die Künstler: Al, Hansen, Geoff Hendricks, Joe Jones, Allan Kaprow, George Maciunas, Charlotte Moorman, Nam June Paik, Takako Saito, Carolee Schneemann, Daniel Spoerri, Ken Friedman, Walter Marchetti, Larry Miller, Robin Page, Ben Patterson, Ben Vautier, Ay-o, George Brecht, Milan Knizaul Sharits, Yoshi Wada, e.a.
Fluxus Subjektiv, Galerie Krinzinger, Wien, 21. September - 3. November 1990.
Duits & Engels
kunstcatalogus
Keywords: Friedman, Ken; Nitsch, Hermann; Vautier, Ben; Knizak, Milan; Kowanz, Brigitte; Weibel, Peter; Conz, Francesco